Not only causation in the physical world: pseudocausation also matters - Quezada, Wilfredo; Pavez F., Luis (Revista de Humanidades de Valparaíso, 2016)
In this essay we show that some thesis -contended by some authors searching on physical causation- about causal pseudoprocesses, processes of which the most salient aspect seems to be travelling faster than the speed of light, must be rejected o seriously modified. Secondly, we will argue that there is just one non causal entities category and that special relativity does not provide any particular motivation to appeal to an ontological distinction based on identity over time. In addition, this conclusion we will enable us to offer a more accurate definition of a pseudoprocess than that found in the relevant literature. In third place, we will show in some detail how such processes, understood the way that we suggest here, are and have been valuable methodological tools when studying –through usual measurement procedures- effective causal relations holding in the physical world. Finally, we will connect our conclusions with R. Torretti’s criticism on the relation between ordinary causation and governed-by-differential-equations physical processes and we will show that, although neutral on his anthropocentric background, the account here argued provides, against what Torretti claims, a natural explanation to the physical connection between ordinary causation and causal processes such as studied by physics.